Dynamic changes in insulin and glucagon during disease progression in rhesus monkeys with obesity‐related type 2 diabetes mellitus. Issue 5 (22nd January 2019) - Wang, Can; Xiao, Yao; Wang, Jue; Hou, Ning; Cui, Weiyi; Hu, Xiaomin; Zeng, Fanxin; Yuan, Ye; Ma, Dongwei; Sun, Xueting; Zhang, Yan; Zheng, Wen; et al.
Abstract : Aims: To investigate the progression of obesity‐related type 2 diabetes mellitus (T2DM) in rhesus monkeys, especially dynamic changes in insulin and glucagon. Materials and methods: We followed a cohort of 52 rhesus monkeys for 7 years throughout the progression of obesity‐related T2DM. Intravenous glucose tolerance tests were performed every 6 months to evaluate dynamic changes in glucose, insulin and glucagon levels. Results: Obesity in rhesus monkeys increased the overall mortality and T2DM morbidity. During the progression of T2DM, glucagon remained consistently elevated, while insulin initially increased in compensation but then dropped to below normal levels when the monkeys developed overt T2DM. After a glucose challenge, both the first and second phases of insulin secretion increased during the early stage of T2DM; in later stages the first phase was delayed and the second phase was diminished. Conclusion: Our findings showed that, beside the decreased insulin level, hyperglucagonaemia also plays an important role in the development of T2DM.